The Teachers' voice in Saxony-Anhalt: perspectives on transition from primary to secondary school. Issue 2 (15th March 2018) - Chambers, Gary
ABSTRACT: Preparation and provision for transition between primary and secondary school get mixed reviews across all subjects. The literature suggests that modern languages is an area deserving particular attention. There are examples of good practice in transition, but the general picture is, at best, patchy. Researchers [e.g. Blondin, C., M. Candelier, P. Edelenbos, R. Johnstone, A. Kubanek-German, and T. Taeschner. 1998. Foreign Languages in Primary and Pre-school Education . London: Centre for Information on Language and Teaching Research; Hill, K., A. Davies, J. Oldfield, and N. Watson. 1998. Questioning an early start: the transition from primary to secondary foreign language learning. Melbourne Papers in Language Testing 6, no. 2: 21–36; Rosenbusch, M. 1995. Language learners in the elementary school: investing in the future. In Foreign language learning: The Journey of a Lifetime, ed. R. Donato and R. Terry, 1–32. Lincolnwood, IL: National Textbook] confirm that this is not a country-specific issue, but one which crosses borders of countries and continents. The purpose of this article is to report on how schools in Saxony-Anhalt, Germany, have dealt with the challenge of transition. The outcomes of semi-structured interviews with 25 secondary schools teachers suggest that many of the problems in Saxony-Anhalt are the same as for other countries, not least in relation to communication between secondary and primary schools and the exchange of information on individual pupils. Our German neighbours offer models of good practice in relation to continuing professional development, clearly defined and understood teaching content and methods and the avoidance of any need for pupils to start their modern language learning experience afresh on arrival at secondary school.